Rapid burst of H2O2 by plant growth regulators increases intracellular Ca2+ amounts and modulates CD4+ T cell activation - Ahmed, A; Mukherjee, S; Deobagkar, M; Naik, T; Nandi, D (Elsevier, 2010)
The identification of small molecules that affect T cell activation is an important area of research. Three molecules that regulate plant growth and differentiation, but not their structurally similar analogs, were identified to enhance primary mouse CD4(+) T cell activation in conjunction with soluble anti-CD3 stimulation: Indoleacetic acid (natural plant auxin), 1-Napthaleneacetic acid (synthetic plant auxin) and 2,4-Dichlorophenoxyacetic acid (synthetic plant auxin and herbicide). These effects are distinct in comparison to Curcumin, the well known phenolic immunomodulator, which lowers T cell activation. An investigation into the mechanisms of action of the three plant growth regulators revealed a rapid induction of reactive oxygen species (ROS), mainly comprising H(2)O(2). In addition, these three molecules synergize with soluble anti-CD3 signaling to enhance intracellular Ca(2+) concentrations [Ca(2+)](i), leading to greater T cell activation, e.g. induction of CD25 and IL-2. Enhanced production of TNFα and IFNγ by CD4(+) T cells is also observed upon plant growth regulator treatment with soluble anti-CD3. Interestingly, maximal IL-2 production and CD4(+) T cell cycle progression are observed upon activation with soluble anti-CD3 and phorbol 12-myristate 13-acetate (PMA), a phorbol ester. Additionally, stimulation with PMA and Ionomcyin (a Ca(2+) ionophore), which activates T cells by circumventing the TCR, and plant growth regulators also demonstrated the role of the strength of signal (SOS): T cell cycle progression is enhanced with gentle activation conditions but decreased with strong activation conditions. This study demonstrates the direct effects of three plant growth regulators on CD4(+) T cell activation and cycling.